Apple gene pool use, sources and donors of economically valuable traits - E. N. Sedov (Вавиловский журнал генетики и селекции)
The significance of an apple genetic collection and its use in the development of new adaptive apple cultivars meeting up-to-date requirements are investigated. Nevertheless, the genetic diversity of existing collections is shown to be still insufficiently used in breeding institutions. McIntosh, Jonathan, Wealthy, Golden Delicious, Melba, Antonovka Obyknovennaya, Ranetka Purpurovaya, and Papirovka are valuable parental varieties in apple breeding, used in Russia and worldwide. In spite of the availability of a large genetic collection, only 48 cultivars were used as initial parental forms when developing about 50 apple varieties (according to the All-Russia Research Institute of Fruit Crop Breeding). That makes up less than 7% of the gene pool of over 700 cultivars kept at the Institute. Among 10 most valuable sources of new varieties are McIntosh (12), scab immune Seyanetz 814 (9), Antonovka Obyknovennaya (7), Papirovka Tetraploid (11), etc. We recommend sources and donors for apple breeding for commercially valuable traits (winter hardiness, columnar tree type, precocity and high productivity, long fruit storability, high resistance and immunity to scab), as well as donors of diploid gametes for triploid cultivar breeding, sources and donors of high contents of sugars, titrated acids and biologically active substances (ascorbic acid and P-active substances) in fruits.The necessity of selection and breeding of complex sources and donors possessing two and more valuable traits (immunity to scab and tetraploidy, immunity to scab and the columnar tree type, etc.) is discussed.